RECOVER study: a multicenter retrospective cohort study and comparison of the efficacy and safety of clazosentan and fasudil in patients with aneurysmal subarachnoid hemorrhage - Muraoka, Shinsuke; Izumi, Takashi; Nishida, Kazuki; Chrétien, Basile; Ishii, Kazuki; Takeuchi, Issei; Nishihori, Masahiro; Goto, Shunsaku; Maesawa, Satoshi; Shimato, Shinji; Kinkori, Takeshi; Asai, Takumi; et al. (Journal of neurosurgery, 2025)
OBJECTIVE: Delayed cerebral ischemia (DCI) is a crucial determinant of the prognosis of patients with aneurysmal subarachnoid hemorrhage (aSAH). In Japan, fasudil has traditionally been used to prevent cerebral vasospasm after aSAH. The effectiveness of clazosentan, a selective endothelin receptor A antagonist, in preventing cerebral vasospasm, a significant contributor to DCI, was recently demonstrated. This study aimed to compare the efficacy and safety of perioperative management using clazosentan- and fasudil-based therapies. METHODS: This multicenter, retrospective observational cohort study included 466 patients with aSAH. Patients were categorized into two groups based on the perioperative management administered: clazosentan or fasudil. Data on patient characteristics, treatment outcomes (assessed using the modified Rankin Scale [mRS] at discharge), and complications (including angiographic cerebral vasospasm, vasospasm-related DCI, pulmonary complications, hypotension, brain edema, and de novo intracerebral hemorrhage) were collected. Statistical analyses were conducted using inverse probability of treatment weighting to adjust for selection bias. RESULTS: Clazosentan was significantly more effective than fasudil in preventing angiographic cerebral vasospasm (33.7% of fasudil-treated patients had vasospasm vs 15.4% of clazosentan-treated patients, p < 0.001) and vasospasm-related DCI (10.2% fasudil vs 4.4% clazosentan, p = 0.007). This improved effectiveness resulted in significantly better outcomes at discharge (50.5% of fasudil-treated patients had an mRS score of 0-2 vs 62.2% of clazosentan-treated patients, p = 0.005). Although clazosentan has been reportedly associated with fluid retention complications, no significant differences in the incidence rates of pulmonary complications or brain edema were found between the groups in this study, likely because of improved fluid management protocols. Clazosentan may also be effective in severe cases or for use in elderly patients aged ≥ 75 years. CONCLUSIONS: Clazosentan outperformed fasudil in preventing cerebral vasospasm and improving overall outcomes in patients with aSAH. Despite initial concerns regarding fluid retention, appropriate perioperative management mitigated these risks, making clazosentan a superior treatment option across different patient groups.